Pregunta
\( 30 x^{2}+2 x-24=0 \) \( 0 x^{2}-2 x-15=0 \) \( 02 a^{2}-11 x-6=0 \) H/W \( =1 \) (d) \( x^{2}+6 x=1 \) \( x^{2}-4 x-=0 \)
Ask by Mcguire Welch. in South Africa
Feb 03,2025
Solución de tutoría real
Respuesta verificada por el tutor
Responder
Solutions to the equations are as follows:
1. \( x = \frac{-1 \pm \sqrt{721}}{30} \) or approximately \( x \approx 0.8617 \) and \( x \approx -0.9283 \)
2. \( x = -7.5 \)
3. \( x = -\frac{6}{11} \approx -0.5455 \)
4. \( x = -3 \pm \sqrt{10} \) or approximately \( x \approx 0.1623 \) and \( x \approx -6.1623 \)
5. If the equation is \( x^{2} - 4x = 0 \), then \( x = 0 \) and \( x = 4 \)
Please provide more information for the third equation if needed.
Solución
Sure, I'd be happy to help you solve these quadratic equations. Let's go through each one step by step. I'll also address any apparent typos or ambiguities to ensure accurate solutions.
---
### 1. \( 30x^{2} + 2x - 24 = 0 \)
**Simplify the Equation:**
First, let's see if we can simplify the equation by dividing all terms by a common factor. In this case, we can divide by 2:
\[
30x^{2} + 2x - 24 = 0 \\
\Rightarrow 15x^{2} + x - 12 = 0
\]
**Solve Using the Quadratic Formula:**
The quadratic formula is:
\[
x = \frac{-b \pm \sqrt{b^2 - 4ac}}{2a}
\]
For the equation \(15x^{2} + x - 12 = 0\):
- \( a = 15 \)
- \( b = 1 \)
- \( c = -12 \)
**Calculate the Discriminant (\( D \)):**
\[
D = b^2 - 4ac = 1^2 - 4 \times 15 \times (-12) = 1 + 720 = 721
\]
**Find the Roots:**
\[
x = \frac{-1 \pm \sqrt{721}}{2 \times 15} = \frac{-1 \pm \sqrt{721}}{30}
\]
\[
\sqrt{721} \approx 26.85
\]
**Approximate Solutions:**
\[
x \approx \frac{-1 + 26.85}{30} \approx \frac{25.85}{30} \approx 0.8617
\]
\[
x \approx \frac{-1 - 26.85}{30} \approx \frac{-27.85}{30} \approx -0.9283
\]
**Exact Solutions:**
\[
x = \frac{-1 \pm \sqrt{721}}{30}
\]
---
### 2. \( 0x^{2} - 2x - 15 = 0 \)
**Interpretation:**
Since the coefficient of \( x^2 \) is 0, this is a linear equation, not a quadratic one.
**Simplify the Equation:**
\[
-2x - 15 = 0 \\
\Rightarrow -2x = 15 \\
\Rightarrow x = -\frac{15}{2} \\
\Rightarrow x = -7.5
\]
**Solution:**
\[
x = -7.5
\]
---
### 3. \( 02a^{2} - 11x - 6 = 0 \) (Assuming H/W \(=1\))
**Clarification Needed:**
There appear to be some typos or ambiguities in this equation:
- **"02a²"**: This could mean \(0 \times 2a^2 = 0\), reducing the equation to \(-11x - 6 = 0\).
- **Variables Mixed**: The equation has both \( a \) and \( x \), which is unusual unless it's a system of equations or relates to homework 1.
**Assuming It’s a Linear Equation in \( x \):**
If we consider \(02a^{2} = 0\), then:
\[
-11x - 6 = 0 \\
\Rightarrow -11x = 6 \\
\Rightarrow x = -\frac{6}{11}
\]
**Solution:**
\[
x = -\frac{6}{11} \approx -0.5455
\]
*If there’s more context or if \( a \) is involved in another part of the problem, please provide additional details.*
---
### 4. (d) \( x^{2} + 6x = 1 \)
**Rewrite in Standard Quadratic Form:**
\[
x^{2} + 6x - 1 = 0
\]
**Solve Using the Quadratic Formula:**
\[
x = \frac{-b \pm \sqrt{b^2 - 4ac}}{2a}
\]
Here:
- \( a = 1 \)
- \( b = 6 \)
- \( c = -1 \)
**Calculate the Discriminant (\( D \)):**
\[
D = 6^2 - 4 \times 1 \times (-1) = 36 + 4 = 40
\]
**Find the Roots:**
\[
x = \frac{-6 \pm \sqrt{40}}{2 \times 1} = \frac{-6 \pm 2\sqrt{10}}{2} = -3 \pm \sqrt{10}
\]
**Approximate Solutions:**
\[
\sqrt{10} \approx 3.1623 \\
x \approx -3 + 3.1623 \approx 0.1623 \\
x \approx -3 - 3.1623 \approx -6.1623
\]
**Solutions:**
\[
x = -3 + \sqrt{10} \quad \text{and} \quad x = -3 - \sqrt{10}
\]
---
### 5. \( x^{2} - 4x - = 0 \)
**Clarification Needed:**
There's an incomplete term in this equation: \( x^{2} - 4x - \quad = 0 \). It seems like a value is missing after the second minus sign. I'll consider two possible interpretations:
#### **a. Missing Constant Term:**
If the equation is \( x^{2} - 4x = 0 \):
**Factor the Equation:**
\[
x(x - 4) = 0
\]
**Find the Roots:**
\[
x = 0 \quad \text{or} \quad x = 4
\]
**Solutions:**
\[
x = 0 \quad \text{and} \quad x = 4
\]
#### **b. Typographical Error with a Constant:**
If the equation was intended to have a constant, for example, \( x^{2} - 4x - c = 0 \), where \( c \) is a number, please provide the value of \( c \) to solve accordingly.
---
**Summary of Solutions:**
1. \( 30x^{2} + 2x - 24 = 0 \)
- Exact: \( x = \frac{-1 \pm \sqrt{721}}{30} \)
- Approximate: \( x \approx 0.8617 \) and \( x \approx -0.9283 \)
2. \( 0x^{2} - 2x - 15 = 0 \)
- \( x = -7.5 \)
3. \( 02a^{2} - 11x - 6 = 0 \) (Assuming linear in \( x \))
- \( x = -\frac{6}{11} \approx -0.5455 \)
4. \( x^{2} + 6x = 1 \)
- Exact: \( x = -3 \pm \sqrt{10} \)
- Approximate: \( x \approx 0.1623 \) and \( x \approx -6.1623 \)
5. \( x^{2} - 4x - = 0 \)
- If \( x^{2} - 4x = 0 \): \( x = 0 \) and \( x = 4 \)
---
If you have any further information or specific questions about these problems, feel free to ask!
Revisado y aprobado por el equipo de tutoría de UpStudy
Como
error msg
Explicar
Simplifique esta solución
Beyond the Answer
To tackle that first equation, let’s factor it! The quadratic \(30x^2 + 2x - 24 = 0\) can be simplified using the quadratic formula, \(x = \frac{-b \pm \sqrt{b^2 - 4ac}}{2a}\). Here, \(a = 30\), \(b = 2\), and \(c = -24\). Plugging those values in will unveil your roots in a jiffy! Now, turning to the equation \(x^2 + 6x = 1\), you’ll want to rearrange it into standard form: \(x^2 + 6x - 1 = 0\). This fun quadratic can also be solved using the quadratic formula or completing the square to find the value of \(x\). Good luck finding those roots!
¡Prueba Premium ahora!
¡Prueba Premium y hazle a Thoth AI preguntas de matemáticas ilimitadas ahora!
Quizas mas tarde
Hazte Premium